Employee Recruitment Process: A Case On A Telecommunication Companies In Indonesia - Rohmatuningsih, Hera (International Publisher (YAPENBI), 2022)
The purpose of this study is to find out how the employee recruitment process is carried out by telecommunications companies in Indonesia. To find out the obstacles that occur in the employee recruitment process carried out by telecommunications companies in Indonesia. To find out what solutions are obtained from these existing constraints. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the production administration process in metal metal companies. This research requires data related to the author's study which is sourced from literature studies, field studies, documentation techniques. The results of the research regarding the employee recruitment process at telecommunications companies in Indonesia are as follows: Starting from the user submits a request for labor to HRD. HRD receives, checks and then submits it to BOD. If the BOD agrees, a job vacancy will be opened. HRD will make a selection, after the recruitment process is complete. The new employee will undergo a probationary period and a performance appraisal will be carried out on the new employee. If during the probationary period the new employee's performance appraisal is good, he will be appointed as a permanent employee. Barriers in the employee recruitment process are as follows: Recruitment of employees for positions that have certain qualifications is difficult to obtain in a short time, some candidate telephone numbers are difficult to contact, limited storage space for documents that hinders the recruitment process, the number of candidates who come for written tests and the interview did not match the person contacted. Solutions in solving problems or obstacles are as follows: HRD will seek information from other companies and will inform the relevant department whether the problem or obstacle takes a long time or not. If the candidate's number is difficult to contact, they will be contacted via e-mail and sms. The company provides a special storage room for the personnel division. Re-contact candidates who are unable to attend to reschedule the written test and interview schedule.